Covid-19 conceptual metaphors in Jordanian political discourse : evidence from a newspaper-based corpus - El-Kanash, Hanan Hasan; Hamdan, Jihad M. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Conceptual Metaphors are part of human cognition and are essential to human knowledge and experience. The study reported here examines the COVID-19 conceptual metaphors underlying the metaphoric language employed by Jordanian government officials during two periods in 2020, namely from February to May and September to December. To this end, a corpus of official statements (n=213) reported in Al-Rai ‘The Opinion’, an Arabic daily mainstream newspaper, was collected and analyzed using the Cognitive Metaphor Theory proposed by Lakoff and Johnson (1980, 2003). Identified conceptual metaphors are categorized under the following eight source domains: WARFARE, CONTAINER, OCEAN, JOURNEY, NATURAL PHENOMENON, EXAMINATION, ANIMAL, and SPORT. A comparison of the frequency of these metaphors in each period is established. The analysis reveals that WARFARE and CONTAINER metaphors have the highest frequency in both periods followed by OCEAN and JOURNEY. The percentage of the other four domains is less than five percent. Conceptual metaphors subsumed under the frequent domains, namely, WARFARE, CONTAINER, OCEAN, and JOURNEY are further examined and discussed following Critical Metaphor Analysis (Charteris-Black 2004). The results show that during the first period, the priority given by the Jordanian government was to focus on convincing people of the restrictive measures which suspended freedom. Therefore, WARFARE has dominated the scene. However, as the crisis progressed, the CONTAINER metaphors took over. This study may assist government agencies to use the right metaphors to impact the public opinion and win the masses to their stands.